" They don't want our blood" Social inclusion and blood donation among African migrants in Australia - Polonsky, M.; Brijnath, Bianca; Renzaho, A. (Pergamon Press, 2011)
The current study examines how feelings of social inclusion influence migrant communities' predisposition to donate blood, focusing specifically on Sub-Saharan African communities in Australia. We begin by explicating the theoretical links between social inclusion, citizenship and blood donation before discussing local and international perspectives of blood donation among African migrant communities. Using qualitative methods comprising nine focus group discussions, held between March and April 2010, we argue that blood donation intentions are mediated by whether or not individuals feel included in their new host society. Real and perceived discrimination experienced by African migrants in their everyday social interactions or in institutional settings can act as a barrier to blood donation. We conclude that removing such barriers, thereby increasing rates of donation in migrant communities, will help to build social capital and inclusion. Strategies for how this can be achieved are outlined.